Unstable ground: climate change, conflict, and genocide - Alvarez, Alex (Studies in genocide: religion, history, and human rights, 2021)
Introduction -- Making Sense of Climate Change -- On the Origins of Violent Conflict: War and the Genocidal Impulse -- Linking Climate Change and Conflict -- Water, Violent Conflict, and Genocide -- Forced Displacement and Borders in a Warming World -- Preventing Conflict and Building Resilience.